Tests of flow characteristics for a model ball valve - Gil, Stanisław; Wnęk , Mariusz; Łudzień , Robert (Instal, 2019)
The investigations of the dynamics of the flow characteristics for the model ball valve at the laboratory unit are described in the paper. In the experiments, according to the selected procedures, the effects of the drive speed on the specific characteristics were determined. The use of a “slower” drive system (i.e. longer flow time) narrows the characteristics in terms of reduction of the difference in flow measures between the course of opening and closing of the valve. The interim stops additionally affect the flow measurements up to their equalization for the course of opening and closing (which is ensured by the variable speed actuator). In the specified test procedure of the dynamic characteristics of flow measurement, the effect of the flow meter measurement transducer on the characteristics course was assessed. It was observed that faster operation of the transducer results in closer records of fluid mass flow for the opening and closing procedures. The method of approximation of characteristics obtained and the principle of its use for control processes were also presented. The experiments clearly suggest the importance of proper adjustment of the measurement and control systems due to flow characteristics that essentially affect the process of flow technology system control.